2007
DOI: 10.1002/anie.200604965
|View full text |Cite
|
Sign up to set email alerts
|

Direct Monitoring of Formation and Dissociation of Individual Metal Complexes by Single‐Molecule Fluorescence Spectroscopy

Abstract: For the observation of the coordination states of individual copper(II) chelate complexes in thermodynamic equilibrium (see picture; TMR=tetramethylrhodamine), single‐molecule fluorescence spectroscopy can be used. Application of time‐resolved single‐molecule spectroscopy opens new prospects for the investigation of reactions in the coordination sphere of metal complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 17 publications
0
48
0
Order By: Relevance
“…Besides photobleaching, dark states represent a main concern in many biomolecular single-molecule studies. Dark states often originate from stochastic transitions to the triplet state (17), or from radical ion states formed as a result of electron transfer reactions (18)(19)(20)(21). Recently, an improved understanding of the underlying (redox) processes has led to ways to suppress photobleaching as well as triplet-and redox-blinking (22,23).…”
mentioning
confidence: 99%
“…Besides photobleaching, dark states represent a main concern in many biomolecular single-molecule studies. Dark states often originate from stochastic transitions to the triplet state (17), or from radical ion states formed as a result of electron transfer reactions (18)(19)(20)(21). Recently, an improved understanding of the underlying (redox) processes has led to ways to suppress photobleaching as well as triplet-and redox-blinking (22,23).…”
mentioning
confidence: 99%
“…Additionally, the 5'-end of the TMR-labelled oligonucleotide was conjugated with biotin to allow immobilization on streptavidincoated surfaces (Figure 4 a). [48] After imaging and localising individual probes by raster line scanning with the confocal microscope (Figure 4 b), individual probes were positioned one after another in the focal volume for time-resolved acquisition of their fluorescence as shown in Figure 4 c. [48,49] While the fluorescence traces in absence of Cu 2 + typically show constant fluorescence until photobleaching, the presence of Cu 2 + induces flickering of the fluorescence emission due to individual binding events on the bipyridine residue (Figure 4 c). This was the first time that single-molecule fluorescence spectroscopy was used to directly monitor individual association and dissociation events of metal-ion coordination to an organic ligand.…”
Section: Metal(ii) Coordination On Bipyridin Ligands Probed By Electrmentioning
confidence: 99%
“…The rates derived from the exponential fit are 16.6 s -1 for the complex formation and 4 s -1 for the complex dissociation, which is in good accordance to the experimental data derived with the TMR sensor. 7 Dividing the examined rate by the applied concentration of copper (II) the association rate constant is derived k a = 5.5 x 10 6 M -1 s -1 . As the dissociation is a first order reaction the observed rate equals the rate constant k d = 4 s -1 .…”
Section: Single-molecule Studies With Atto620 Labeled Probementioning
confidence: 99%
“…6 Very recently, we developed a metal sensor using tetramethylrhodamine (TMR) as reporter dye that was strongly quenched by the formation of a Cu 2+ -complexes in close vicinity. 7 We determined a quenching constant of 4.2 x 10 6 M -1 using fluorescence ensemble spectroscopy. For the first time, we demonstrated that SMFS, a method which has proven its advantages to investigate processes in biological samples 8 and photophysical properties of chromophores [9][10][11] , was used to determine rate constants of complex formation and dissociation.…”
Section: Introductionmentioning
confidence: 99%